Analysis of the effect of price and quality of service on customer satisfaction RedDoorz Hotel Jakarta - Arnita Putri Nurwahyuni; Aziz Fauzi Arief; Bellie Saputra; Christina Melatikesuma; Frederick Moses; Ilham Dwi Prasetyo; Muhammad Rafi Ananda; Sinta Supinah (Privietlab, 2021)
Service quality is one of the most important factors in running a business, because good service quality will increase customer satisfaction and the development of a business. The minimum facilities that are always available at RedDoorz are clean linen, free WiFi, Mineral water, AC, clean toilet, towels, water heater, and 24/7 service. After permanently improving the quality of lodging to meet the main standards of RedDoorz lodging products, RedDoorz is responsible for assisting online and offline room sales. RedDoorz conducts large-scale sales by deploying all corporate sales programs. In a cooperative relationship, RedDoorz guarantees transparency and clear contracts with all innkeepers. The finding is an assessment of whether the tested hypothesis is accepted or rejected. The decision taken is accepted, that actually according to the research above, Service Quality and Price do not affect Visitor Satisfaction with a percentage value that tends to be small in its role using validity tests and simple regression along with classical assumption tests.